Identification and validation of QTL for spike fertile floret and fruiting efficiencies in hexaploid wheat (Triticum aestivum L.) - Pretini, Nicole; Vanzetti, Leonardo Sebastian; Terrile, Ignacio Ismael; Börner, Andreas; Plieske, Jörg; Ganal, Martin; Röder, Marion; Gonzalez, Fernanda Gabriela (Springer, 2020)
The spike fruiting efficiency (FE—grains per unit spike dry weight at anthesis, GN/SDW) is a promising trait to improve wheat yield potential. It depends on fertile floret efficiency (fertile florets per unit SDW—FFE, FF/SDW) and grain set (grains per fertile floret—GST). Given its difficult measurement, it is often estimated as the grains per unit of nongrain spike dry weight at maturity (FEm). In this study, quantitative trait loci (QTL) were mapped using a double haploid population (Baguette 19/BIOINTA 2002, with high and low FE, respectively) genotyped with the iSelect 90 K SNP array and evaluated in five environments. We identified 37 QTL, but two were major with an R2 > 10% and stable for being at least present in three environments: the QFEm.perg-3A (on Chr. 3A, 51.6 cM, 685.12 Mb) for FEm and the QFFE.perg-5A (on Chr. 5A, 42.1 cM, 461.49 Mb) for FFE, FE and FEm. Both QTL were validated using two independent F2 populations and KASP markers. For the most promising QTL, QFFE.perg-5A, the presence of the allele for high FFE resulted in + 4% FF, + 9% GN, + 13% GST, + 16% yield gSDW−1 and + 5% yield spike−1. QFEm.perg-3A and QFFE.perg-5A represent two new loci to use in MAS to improve wheat yield potential.